2001
DOI: 10.1161/hc5001.101966
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Contractile Function and Heart Rate in Mice With Myocyte-Specific Overexpression of Endothelial Nitric Oxide Synthase

Abstract: Background-The major source of nitric oxide (NO) in the heart is the constitutive form of NO synthases (eNOS, NOS III) that is expressed in vascular endothelium and cardiac myocytes. NO mediates endothelium-dependent vasodilation and may modulate cardiac function. We examined the role of NO in hearts from transgenic (TG) mice overexpressing eNOS exclusively in cardiac myocytes. Methods and Results-Three independent TG lines with varying levels of NOS activity were selected, and the hearts were isolated and ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
85
2
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(97 citation statements)
references
References 35 publications
9
85
2
1
Order By: Relevance
“…Viral delivery of NOS3 with a cardiac-specific ␣-MyHC promoter restored the increased systolic pressure and decreased relaxation rate observed in NOS3 knockout mice back toward wild type, and the enhanced ␤-AR-mediated contractile function observed with this knockout model also returned to wildtype levels. Similar results were observed in a NOS3 overexpression transgenic model (87). The basis for these divergent outcomes is not known, but it may result from the level of NOS3 expression or the reduced transfection efficiency in the in vivo versus in vitro models.…”
Section: Nos3 or Endothelial Nossupporting
confidence: 66%
“…Viral delivery of NOS3 with a cardiac-specific ␣-MyHC promoter restored the increased systolic pressure and decreased relaxation rate observed in NOS3 knockout mice back toward wild type, and the enhanced ␤-AR-mediated contractile function observed with this knockout model also returned to wildtype levels. Similar results were observed in a NOS3 overexpression transgenic model (87). The basis for these divergent outcomes is not known, but it may result from the level of NOS3 expression or the reduced transfection efficiency in the in vivo versus in vitro models.…”
Section: Nos3 or Endothelial Nossupporting
confidence: 66%
“…Because each component within the complex contributes to the complex formation, it is very likely that expression changes in Akt and/or eNOS may also influence assembly of this module. Consequently, future studies are required to investigate Akt-and eNOS-induced changes in PKCε-Akt-eNOS module formation, potentially with use of transgenic mouse models with cardiac-specific overexpression of Akt or eNOS (6,9).…”
Section: Discussionmentioning
confidence: 99%
“…For example, mice with specific knockout of NOS3 (NOS3 Ϫ/Ϫ ) have an increased response to ␤-AR stimulation (4,11,19,20,47). Similarly, transgenic mice with cardiac myocyte-specific NOS3 overexpression have a decreased response to ␤-AR stimulation (9,23). Although the vast majority of studies found the above effects, it should be noted that a few studies observed dissimilar results (29,46).…”
mentioning
confidence: 99%